2015
DOI: 10.5935/1518-0557.20150030
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of Human Oocytes and its Contribution to In Vitro Fertilization Programs

Abstract: Objeticve: To study the cumulative pregnancy outcome, particularly in terms of live births, with the consecutive transfer of embryos from fresh and vitrified/warmed oocytes to infertile patients in a routine infertility program. Methods: Patients were initially submitted to in vitro fertilization embryo transfer with fresh embryos, while surplus oocytes were vitrified with the Vitri-Ingá method. Patients who did not succeed to carry their gestation to term underwent a new cycle with embryos from their own warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
7
0
1
Order By: Relevance
“…Vitrification is a rapidly developing technology that is increasingly being used for the cryopreservation of gametes, embryos (particularly blastocysts) and germinative tissue. Vitrification has already been demonstrated to be a reliable strategy for the cryopreservation of embryos (Almodin et al, 2010) and oocytes (Cobo et al, 2008;Cobo et al, 2010;Almodin et al, 2015). Since the development and consolidation of vitrification as an alternative to slow-freezing technique, efforts have now been focused on the development of vitrification devices and supplies that can enable the cryopreservation of germinative tissue, with results comparable to those already reported for oocytes and embryos.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Vitrification is a rapidly developing technology that is increasingly being used for the cryopreservation of gametes, embryos (particularly blastocysts) and germinative tissue. Vitrification has already been demonstrated to be a reliable strategy for the cryopreservation of embryos (Almodin et al, 2010) and oocytes (Cobo et al, 2008;Cobo et al, 2010;Almodin et al, 2015). Since the development and consolidation of vitrification as an alternative to slow-freezing technique, efforts have now been focused on the development of vitrification devices and supplies that can enable the cryopreservation of germinative tissue, with results comparable to those already reported for oocytes and embryos.…”
Section: Discussionmentioning
confidence: 74%
“…The successful vitrification of embryos (Almodin et al, 2010), oocytes (Almodin et al, 2015), and male germinative tissue (Radaelli et al, 2017) using the Vitroequip method have already been reported by our research team. Radaelli et al (2017), found that the morphology of prepuberal male germinative tissue in rats was adequately cryopreserved with both slow freezing and vitrification.…”
Section: Introductionmentioning
confidence: 61%
“…Based on survival rates of thawing oocytes described in previous studies [4, 6-14, 16, 18, 20, 21, 34], we concluded that vitri cation-thawing program has been standardized. Vitri ed oocytes is a mature technology for reproduction preservation and has similar outcomes to fresh oocytes in donor women [6][7][8][9][10][11][12][13][14][15][16]. But intracellular ice crystals formation, solution effects, and osmotic shock which cause oocytes damage still exit during cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous randomized controlled trials and prospective and retrospective studies have shown that cryopreserved oocytes provide reproductive outcomes comparable to fresh oocytes use [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, large cohort analysis has indicated overall lower reproductive outcomes using vitri ed donor oocytes rather than using fresh donor oocytes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Una de sus principales desventajas es la problemática legal, ya que requiere del consentimiento de ambos padres biológicos para su uso, sin dejar de lado la cuestión ética que supone el futuro incierto de embriones abandonados. 29…”
Section: Criopreservación De Embrionesunclassified